2020
DOI: 10.1097/mlr.0000000000001394
|View full text |Cite
|
Sign up to set email alerts
|

Relative Cost Differences of Initial Treatment Strategies for Newly Diagnosed Opioid Use Disorder

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…10,28 Notably, detoxification and inpatient treatment, common points of initial treatment-seeking for individuals with OUD, are expensive, and associated costs may deter seeking outpatient follow-up. 29,30 While these services are important for some individuals, it is possible to initiate MOUD in an outpatient setting first. Delivery systems and benefit designs should be redesigned to promote low-threshold MOUD initiation and uptake.…”
Section: Discussionmentioning
confidence: 99%
“…10,28 Notably, detoxification and inpatient treatment, common points of initial treatment-seeking for individuals with OUD, are expensive, and associated costs may deter seeking outpatient follow-up. 29,30 While these services are important for some individuals, it is possible to initiate MOUD in an outpatient setting first. Delivery systems and benefit designs should be redesigned to promote low-threshold MOUD initiation and uptake.…”
Section: Discussionmentioning
confidence: 99%
“…We then captured total, in-person, and telemedicine OUD visits within 90 days of an index visit. For MOUD prescribing, consistent with a previous study, 7 we defined 2 measures of MOUD initiation: (1) the proportion of patients with OUD with initiation within 90 days of the index visit, and (2) the proportion of patients with OUD with initiation within 14 days of the index visit. Retention of MOUD was defined as at least 1 additional MOUD fill within 30 to 90 days of initiation among those with initiation within 14 days of the index visit.…”
Section: Study Outcomesmentioning
confidence: 99%
“…Medications for opioid use disorder (MOUD), which include methadone, buprenorphine, and longacting injectable naltrexone, are considered the most effective treatments available for OUD. [3][4][5][6][7][8][9][10] However, in 2019, the National Survey on Drug Use and Health found that just 27.8% of individuals who needed OUD treatment received MOUD. 11 For decades, there have been long-standing barriers to OUD care, including clinician shortages, stigma, cost, and transportation challenges.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States, approximately $1.02 trillion was spent on opioid use disorders and fatal opioid overdoses in 2017 (4). Incidence of fatal opioid overdose continue to surge in the United States (5). In China, about 1.8 million people use illicit drugs, of which 734,000 are opioid abusers, accounting for 40.8% of it (6).…”
Section: Introductionmentioning
confidence: 99%